Training Future Managers in Russian Business School for Controlling Economic Behavior of Employees at Today’s Corporatio - L. V. Antropova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article grounds the necessity of designing the system of early training of managers with due regard to current trends in market economy. The priority objectives of present business education are managers’ ability to solve managerial problems connected with peculiarities of individual labour behavior of employees. Monitoring research of workers at big corporations showed that more than 70% of employees are motivated for the economic model of behavior in work. The principle cause of their labour activity is the amount of wage. In order to understand the essence of controlling the economic behavior of employee at today’s corporation the author developed a specific model, which includes characteristics of economic behavior of worker, his/her strategy of economic behavior, motivating mechanisms affecting employee’s behavior and leading to higher labour efficiency. On the basis of this model the content of the teaching module ‘Controlling Economic Behavior of Employee at Today’s Corporations’ was developed. It was shownthat training of students should be based on the system approach and a set of subjects by using methods of active training, focused lectures, case-method, imitation projects and students’ participation in business games and communication trainings. Such an approach develops innovation thinking, the ability to apply academic theory in real practical situations. The author identifies the criteria, which could fix different levels of forming control over economic behavior of employees at today’s corporations.